The GPCR-associated sorting protein 1 regulates ligand-induced down-regulation of GPR55 - Kargl, J (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Many GPCRs, including the CB(1) cannabinoid receptor, are down-regulated following prolonged agonist exposure by interacting with the GPCR-associated sorting protein-1 (GASP-1). The CB(1) receptor antagonist rimonabant has also recently been described to be an agonist at GPR55, a cannabinoid-related receptor. Here we investigated the post-endocytic properties of GPR55 after agonist exposure and tested whether GASP-1 is involved in this process. EXPERIMENTAL APPROACH: We evaluated the direct protein-protein interaction of GPR55 with GASP-1 using (i) GST-binding assays and (ii) co-immunoprecipitation assays in GPR55-HEK293 cells with endogenous GASP-1 expression. We further tested the internalization, recycling and degradation of GPR55 using confocal fluorescence microscopy and biotinylation assays in the presence and absence of GASP-1 (lentiviral small hairpin RNA knockdown of GASP-1) under prolonged agonist [rimonabant (RIM), lysophosphatidylinositol (LPI)] stimulation. KEY RESULTS: We showed that the prolonged activation of GPR55 with rimonabant or LPI down-regulates GPR55 via GASP-1. GASP-1 binds to GPR55 in vitro, and this interaction was required for targeting GPR55 for degradation. Disrupting the GPR55-GASP-1 interaction prevented post-endocytic receptor degradation, and thereby allowed receptor recycling. CONCLUSION AND IMPLICATIONS: These data implicate GASP-1 as an important regulator of ligand-mediated down-regulation of GPR55. By identifying GASP-1 as a key regulator of the trafficking and, by extension, functional expression of GPR55, we may be one step closer to gaining a better understanding of this receptor in response to cannabinoid drugs. LINKED ARTICLES: This article is part of a themed section on Cannabinoids in Biology and Medicine. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2012.165.issue-8. To view Part I of Cannabinoids in Biology and Medicine visit http://dx.doi.org/10.1111/bph.2011.163.issue-7